2012
DOI: 10.2147/opth.s34627
|View full text |Cite
|
Sign up to set email alerts
|

Thrombophilia and retinal vascular occlusion

Abstract: PurposeThe purpose of this research was to assess associations of thrombophilia with central retinal vein occlusion (CRVO), central retinal artery occlusion (CRAO), and amaurosis fugax (AF); to evaluate outcomes of normalizing high homocysteine; and to study CRVO, CRAO, and AF developing in estrogens/estrogen agonists in women subsequently shown to have thrombophilia.MethodsMeasures of thrombophilia–hypofibrinolysis were obtained in 132 CRVO cases, 15 CRAO cases, and 17 AF cases. Cases were compared to 105 hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
48
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 55 publications
5
48
0
1
Order By: Relevance
“…Increased risk of CRVO has been associated with deficiency of protein C (Tekeli 1999), protein S (Yap 2007) and antithrombin III (Ririe 1979). Furthermore other studies have reported that factor V Leiden mutation (Rehak 2008) , antiphospholipid (Agarwal 2009) and anticardiolipin syndrome (Glueck 2012) hyperhomocysteinaemia (Cahill 2003) and elevated levels of plasminogen activator inhibitor-1 (Marcucci 2001) may play a role in the etiology of CRVO.…”
Section: Etiologymentioning
confidence: 97%
“…Increased risk of CRVO has been associated with deficiency of protein C (Tekeli 1999), protein S (Yap 2007) and antithrombin III (Ririe 1979). Furthermore other studies have reported that factor V Leiden mutation (Rehak 2008) , antiphospholipid (Agarwal 2009) and anticardiolipin syndrome (Glueck 2012) hyperhomocysteinaemia (Cahill 2003) and elevated levels of plasminogen activator inhibitor-1 (Marcucci 2001) may play a role in the etiology of CRVO.…”
Section: Etiologymentioning
confidence: 97%
“…According to this hypothesis, smoking cessation is recommended. Hyperhomocysteinemia, a thrombophilic state identified and treated in our patient, is an independent risk factor of CRVO [2]. The treatment consists of vitamin supplementation, folic acid 5 mg/day.…”
mentioning
confidence: 73%
“…Complete blood count was normal. Further blood tests revealed hyperhomocysteinemia [2], which has been identified as independent risk fac-tors for the occurrence of recurrent CRVO. The patient was referred to a specialist for a carotid Doppler ultrasound and echocardiography in order to exclude embolic sources.…”
mentioning
confidence: 98%
“…In 2005, a comprehensive meta-analysis found a clear association only with antiphospholipid syndrome and a lesser relationship with factor V Leiden and mutation of the prothrombin gene 13. More recently, a retrospective study of 164 cases found higher levels of homocysteinaemia, anticardiolipin antibodies and inherited factor VIII in addition to lower inherited protein S in RVO compared to controls 14. In a similar mechanism, infectious and inflammatory diseases including hepatitis or cardiac graft rejection have been associated with bilateral vein occlusions 5…”
Section: Discussionmentioning
confidence: 99%